MALT lymphoma of the head and neck: Surgery alone can be an option. (January 2023) - Fu, Rao; Wen, Xutao; Li, Zhengrui; Zhang, Ling
Highlights: MALT lymphoma, as a slowly progressive indolent clinical course, usually occurs in women and is often associated with SS. For MALT lymphoma of the head and neck, surgery alone can achieve favorable results. Abstract: Objectives: To retrospectively analyze the general characteristics of MALT lymphoma in the head and neck and provide clinicians with new ideas for diagnosis and treatment. Materials and Methods: 114 (94.2%) of 121 complete follow-up data were obtained. A single-center retrospective study was conducted on 114 patients with MALT diagnosed from 2010 to 2020. Results: 42 (36.8%) of 114 patients had Sjogren's syndrome before, and there is a significant difference in gender between SS-MALT and non-SS-MALT. As for the treatment method, there is no significant difference in the overall survival between surgery with or without chemoradiotherapy. Conclusion: MALT lymphoma of the head and neck is clinically characterized by a favorable prognosis, always associated with SS. Surgery with or without chemoradiotherapy has little difference in the prolongation of survival time.